Banjar Rice Consumption Dependency Analysis on Kalimantan Selatan People (Jurnal Sosial Ekonomi Pertanian, 2026)
AbstractThe population of South Kalimantan exhibits a strong affinity for the consumption of Banjar rice. Banjar rice originates from local paddy varieties (such as siam, unus, and mayang), which are characterized by a dense, non-sticky (pera), and small-grained texture. However, the productivity of these local varieties is comparatively lower than that of high-yielding varieties, which are currently the primary focus of government production enhancement programs. Consequently, these programs have inadvertently suppressed the production of Banjar rice, leading to a significant increase in its market price. This study aims to determine the extent of South Kalimantan residents' dependency on Banjar rice consumption. The findings are intended to inform the formulation of rice production enhancement programs that align more closely with local wisdom and consumer preferences. The research was conducted across five regencies/cities acting as Cost of Living Survey samples—namely Banjarmasin, Tanah Laut, Kotabaru, Tanjung, and Hulu Sungai Tengah—between January and December 2022. These locations wereCost-of-Livingost-of-Living locations as they adequately represent the consumption patterns of the South Kalimantan population, encompassing urban, rural, mountainous, and coastal areas. A total of 7,200 respondents from these five regions were selected using a stratified random sampling technique, categorized based on the educational background of the household head and the household size. Data analysis was performed using the Quadratic Almost Ideal Demand System – Censorship (QUAIDS-CE) model to obtain the elasticity coefficient matrices, specifically encompassing the own-price elasticity of Banjar rice, cross-price elasticity, and income elasticity. The results indicate that both Banjar and non-Banjar rice exhibit relatively high uncompensated (Marshallian) demand elasticities, but low compensated (Hicksian) demand elasticities. The uncompensated own-price elasticity for Banjar rice is -1.143, indicating that a 1% increase in the price of Banjar rice leads to a 1.143% decrease in its demand. Conversely, the compensated price elasticity for Banjar rice is -0.802 (inelastic, e
Keywords: quaidsce; prices; Banjar rice; Demand